IMPLEMENTASI KEBIJAKAN PEMBANGUNAN PARIWISATA DI KAWASAN TELUK PALU - Mulyadie, Mulyadie (Katalogis, 2015)
The purpose of this study is: To know and analyze the implementation of the policy of tourism development program that has not been effectively involve local communities in the Gulf of Palu. The main theory Willian Dunn policies referenced the theory of Van Meter and Van Horn examines six aspects of standards and policy goals, resources, characteristics of the implementing agency, the attitude tendency (disposition), Activities Implementation & communication between organizations, the economic, social, and political. he place of research in the Gulf Region Palu of Central Sulawesi Province with informants 6 selected people purposive. Collection by way of interviews, observation, and documentation. Data were analyzed using an interactive model of Miles and Huberman. ut the Tourism Development Program Policy Implementation in the Gulf Region Palu seen from 6 aspects there are only two (2) is not maximized, namely (1) Standards and Policies targets that appear on the lack of coordination or cooperation between government and society (2) Resources are inadequate seen of human resources and infrastructure; While the aspect (3) Communication between organizations; where the government and the community can be created through technology (4) karkateristik implementing agency, the policy program of tourism development and the pattern of relations with the implementing agency of the other establishments are sufficient (5) economic conditions, social, and political, it is considered good because the informant had provided food tradsional easily available, the bridge across the river Palu membantang stands to connect or access tranfortasi between Palu Palu West with East, besides also found floating mosques, hotels, shopping centers are increasing travel hasanah Palu bay as a leading tourist attraction in the city of Palu, Central Sulawesi Province , (6) Disposition, basically a tourism development program has been good in the bay of Palu, Palu residents diteluk changes and positive developments in the economy, since tourism began to grow, along with the family began to improve.